Method for increasing the corrosion resistance of highly enriched rare earth permanent magnets by high temperature oxidation treatment.
High-temperature oxidation treatment forms a rare earth oxide thin film on highly concentrated rare earth magnets, enhancing corrosion resistance and magnetic performance by optimizing temperature, time, and oxygen partial pressure, addressing the limitations of existing methods.
Patent Information
- Application Number
- JP2022062187
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-03-02
- Filing Date
- 2022-04-02
- Publication Date
- 2025-02-12
- Estimated Expiration
- 2042-04-02
AI Technical Summary
Existing methods for improving the corrosion resistance of highly concentrated rare earth permanent magnets, such as NdFeB magnets, are inadequate, leading to poor adhesion and contamination issues with protective layers, and neglect the need for enhanced corrosion resistance while maintaining magnetic performance.
A high-temperature oxidation treatment is applied to form a rare earth oxide thin film on the surface of the magnets, controlling parameters like temperature, time, and oxygen partial pressure to enhance corrosion resistance and magnetic properties.
The method effectively increases the corrosion resistance and magnetic performance of highly concentrated rare earth permanent magnets by forming a stable oxide thin film, improving adhesion and mechanical properties without reducing magnetism.
Abstract
Description
[Technical field]
[0001] The present invention relates to the field of corrosion prevention technology, and specifically to a method for increasing the corrosion resistance of highly enriched rare earth permanent magnets by high temperature oxidation treatment. [Background technology]
[0002] From the 1980s to the present, NdFeB permanent magnet material (Neodymium Ferrum Boron permanent magnet material) has the advantage of good comprehensive magnetic performance, and has been widely used in the fields of new energy, information, transportation, medical care and national defense, becoming the most important rare earth functional material and important basic material in the field of national industry. The NdFeB industry has become the fastest developing and largest scale industry in the field of rare earth materials, and uses nearly half of the total amount of rare earth materials used. With the rapid increase in demand for NdFeB materials, the amount of rare earth elements such as Nd, Pr, Dy, Tb, etc., which are in short supply, has also increased significantly. Although there are abundant reserves of highly enriched rare earth elements such as La, Ce, Y, etc., they are not used much in the field of rare earth permanent magnets. Therefore, the research of highly enriched rare earth permanent magnet materials and the use of large amounts of highly enriched rare earth elements such as La, Ce, Y, etc. have attracted attention in the field of rare earth permanent magnets in recent years.
[0003] Compared with NdFeB permanent magnets, the main phase and grain boundary phase of highly enriched rare earth permanent magnets have different components and structures. Due to the different physical and chemical properties of NdFeB permanent magnets and highly enriched rare earth permanent magnets, NdFeB permanent magnets and highly enriched rare earth permanent magnets have different magnetic performance and corrosion resistance. Research has shown that highly enriched rare earth permanent magnets have new corrosion characteristics due to the localized characteristics of the grain boundary phase, which has more complex chemical components, structure and distribution, and therefore has more impact on corrosion resistance than traditional NdFeB. There are two common methods for improving the corrosion resistance of NdFeB permanent magnets. The first method is to increase the electrode potential of the grain boundary phase by alloying, and reduce the potential difference between the electrode potential of the grain boundary phase and the electrode potential of the main phase, but the effect of this method is not significant. The second method is to apply a protective layer on the surface of the magnet to prevent water and other corrosive solutions in the environment that corrode the magnet from adhering to the surface of the magnet. However, the liquid used to apply the protective layer on the surface of the magnet may cause contamination problems, and the adhesion between the protective layer and the NdFeB permanent magnet is not good, so the NdFeB permanent magnet cannot be protected for a long time. When studying high-enriched rare earth permanent magnets, researchers are preoccupied with increasing the magnetic properties of high-enriched rare earth permanent magnets, but often ignore increasing the corrosion resistance of high-enriched rare earth permanent magnets. Increasing the corrosion resistance of high-enriched rare earth permanent magnets while simultaneously increasing the magnetic properties of high-enriched rare earth permanent magnets has become a new and difficult problem to solve. Summary of the Invention [Problem to be solved by the invention]
[0004] SUMMARY OF THE PRESENT EMBODIMENT The objective of the present invention is to provide a method for increasing the corrosion resistance of highly enriched rare earth permanent magnets by high temperature oxidation treatment, in order to overcome the shortcomings of the prior art. [Means for solving the problem]
[0005] In the present invention, a thin film of rare earth oxide is formed on the surface of the highly enriched rare earth permanent magnet at its original position by high-temperature oxidation treatment, thereby increasing the corrosion resistance of the highly enriched rare earth permanent magnet. When the high-temperature oxidation reaction is performed in the heat treatment furnace, the temperature is set to 700 to 1000°C, the reaction time is set to 0.2 to 5 hours, and the oxygen partial pressure during oxidation is set to 10 4 Set it to Pa or less.
[0006] The thickness of the rare earth oxide thin film can be freely changed within the range of 10 nm to 100 μm.
[0007] The components of the highly enriched rare earth permanent magnet are weighed in atomic percentage, and the atomic percentage is (RE a RE' 1-a )x(Fe b M 1-b ) 100-x-y-z M' y B z In the formula, RE is one or more of La, Ce, and Y elements, RE' is one or more of lanthanides other than La, Ce, and Y, Fe is iron element, M is one or two of Co and Ni, M' is one or more of Nb, Zr, Ta, V, Al, Cu, Ga, Ti, Cr, Mo, Mn, Ag, Au, Pb, and Si elements, and B is boron element. a, b, x, y, and z satisfy the following formulas: 0.25≦a≦1, 0.8≦b≦1, 12≦x≦18, 0≦y≦2, and 5.5≦z≦6.5. Effect of the Invention
[0008] Compared with the prior art, the technical features of the present invention can achieve the following inventive effects: (1) In the present invention, the cause of poor corrosion resistance of highly enriched rare earth permanent magnets is detected, and the characteristics of highly enriched rare earth elements La / Ce / Y and other conventional rare earth elements such as Nd / Pr / Dy / Tb are different in phase formation law and diffusion kinetic behavior. Also, the grain boundary rare earth rich phase is easily oxidized. By utilizing this characteristic, a rare earth oxide thin film with good chemical stability can be formed in situ by high-temperature oxidation, and a highly enriched rare earth permanent magnet with good corrosion resistance can be manufactured. In addition, the high-temperature heat treatment can improve the texture of the substrate and improve the magnetic performance. By forming the oxide thin film in situ, the adhesion between the oxide thin film and the substrate can be increased and the mechanical performance can be improved. In the present invention, a method for increasing the corrosion resistance of highly enriched rare earth permanent magnets by high-temperature oxidation treatment is provided, thereby improving the corrosion resistance and magnetic performance. The method of increasing the corrosion resistance of highly concentrated rare earth permanent magnets by high temperature oxidation treatment of the present invention can easily solve the drawbacks of the conventional technology (i.e., the drawback that the corrosion resistance of NdFeB can be improved by adopting the conventional corrosion resistance method of NdFeB (alloying method and surface protection method), but the corrosion resistance and magnetic performance of NdFeB may be deteriorated).
[0009] (2) In highly enriched rare earth permanent magnets with different components, the oxidation process can be designed based on the alloy component design, grain boundary structure, distribution form, physicochemical properties, deformation behavior, and various interface states of the main phase / grain boundary phase, as well as the evolution law of the structure when high-temperature oxidation is performed, and the thickness of the rare earth oxide thin film can be freely changed within the range of tens of nm to tens of μm by adjusting the oxygen partial pressure, oxidation temperature, and reaction time. As a result, high-temperature oxidation technology for highly enriched rare earth permanent magnets can be acquired, and highly enriched rare earth permanent magnet materials with good corrosion resistance, magnetic properties, and mechanical properties can be manufactured.
[0010] (3) The technology of the present invention is unique because it has not yet been disclosed domestically or internationally, and it can solve the problem of poor corrosion resistance that affects the development and application of highly enriched rare earth permanent magnets. In addition, the problem of poor corrosion resistance can be solved only by high-temperature oxidation treatment (700~1000°C), so the process is simple, the cost is low, and it has the advantages of being applicable to mass production.
[0011] (4) After high-temperature oxidation of highly concentrated rare earth permanent magnets, a thin film of rare earth oxide is formed in the original position of the magnet, which makes it possible to obtain a magnet that is dense, continuous, and has good hydrophobicity, and the oxygen partial pressure, oxidation temperature, and reaction time can be precisely controlled. Moreover, the magnet of the present invention does not contain Fe oxides, etc., as NdFeB magnets (Neodymium Ferrum Boron Magnets) do after low-temperature oxidation. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] The present invention will be described in more detail below with reference to specific examples, but the present invention is not limited to the following examples.
[0013] Example 1 The components of a highly enriched rare earth permanent magnet are measured in atomic percentage, and the atomic percentage is [(Pr 0.2 Nd 0.8 ) 0.5 Ce 0.5 ] 13.9 (Fe 0.98 Co 0.02 ) 78.6 (Cu 0.2 Co 0.2 Al 0.3 Ga 0.1 Zr 0.2 ) 1.5 B6. When high-temperature oxidation reaction is performed in the heat treatment furnace, the temperature is set to 900°C, the reaction time is set to 4h, and the partial pressure of oxygen is set to 10Pa. The thickness of the thin film of rare earth oxides formed in the original position on the magnet surface is ~7μm. According to the measurement results of the AMT-4 permanent magnet characteristic measurement device, it can be seen that the residual magnetism of the magnet subjected to the surface oxidation treatment is 12.4kG and the coercive force is 9.0kOe. According to the measurement results of the AMETEK electrochemical workstation, the corrosion current of the magnet subjected to the surface oxidation treatment in 3.5% NaCl solution is 7μA / cm. 2 It can be seen that.
[0014] Comparison 1 The difference between Comparative Example 1 and Example 1 is that the oxygen partial pressure during high-temperature oxidation of the highly enriched rare earth permanent magnet of Comparative Example 1 is 10 5According to the measurement results of the AMT-4 permanent magnet characteristic measuring device, the magnet of Comparative Example 1 has a residual magnetism of 12.3 kG and a coercive force of 8.5 kOe, which are lower than the values of Example 1. According to the measurement results of the AMETEK electrochemical workstation, the corrosion current of the magnet of Comparative Example 1 in a 3.5% NaCl solution is 50 μA / cm 2 It can be seen that the numerical value is larger than that of the first embodiment.
[0015] Comparison 2 The difference between Comparative Example 2 and Example 1 is that the time for which high-enriched rare earth permanent magnets in Comparative Example 2 were subjected to high-temperature oxidation was 10 hours. Measurement results from an AMT-4 permanent magnet property measuring device showed that the magnet in Comparative Example 2 had a residual magnetism of 12.2 kG and a coercive force of 7.9 kOe, both of which were lower than those of Example 1. Measurement results from an AMETEK electrochemical workstation showed that the corrosion current of the magnet in Comparative Example 2 in a 3.5% NaCl solution was 41 μA / cm. 2 It can be seen that the numerical value is larger than that of the first embodiment.
[0016] Comparison 3 The difference between Comparative Example 3 and Example 1 is that high temperature oxidation was not performed on the highly enriched rare earth permanent magnet of Comparative Example 3. According to the measurement results using an AMT-4 permanent magnet characteristic measurement device, the magnet of Comparative Example 3 had a remanence of 12.3 kG and a coercive force of 8.6 kOe, which are lower than those of Example 1. According to the measurement results using an AMETEK electrochemical workstation, the corrosion current of the magnet of Comparative Example 3 in a 3.5% NaCl solution was 82 μA / cm. 2 It can be seen that the value is ten times higher than that of Example 1.
[0017] Comparison 4 The difference between Comparative Example 4 and Example 1 is that in Comparative Example 4, the contents of Cu and Co elements and the highly concentrated rare earth permanent magnet components are increased, and the atomic percentage of the rare earth permanent magnet is [(Pr 0.2 Nd0.8 ) 0.5 Ce 0.5 ] 13.9 (Fe 0.98 Co 0.02 ) 77.1 (Cu 0.4 Co 0.3 Al 0.15 Ga 0.05 Zr 0.1 )3B6, and high temperature oxidation was not performed on the highly enriched rare earth permanent magnet of Comparative Example 4. Measurement results from an AMT-4 permanent magnet characteristic measuring device showed that the magnet of Comparative Example 4 had a residual magnetism of 11.8 kG and a coercive force of 5.7 kOe, which are significantly lower than those of Example 1. Measurement results from an AMETEK electrochemical workstation showed that the corrosion current of the magnet of Comparative Example 4 in a 3.5% NaCl solution was 73 μA / cm 2 It can be seen that the value is ten times higher than that of Example 1.
[0018] Comparison 5 The difference between Comparative Example 5 and Example 1 is that the highly concentrated rare earth permanent magnet of Comparative Example 5 is not subjected to high temperature oxidation, but a plating process is used to form a silver-colored nickel plating layer on the surface of the rare earth permanent magnet, and the thickness of the nickel plating layer is about 7 μm. According to the measurement results using an AMT-4 permanent magnet characteristic measurement device, the magnet of Comparative Example 5 has a residual magnetism of 12.1 kG and a coercive force of 8.1 kOe, which are lower than the values of Example 1. According to the measurement results using an AMETEK electrochemical workstation, the corrosion current of the magnet of Comparative Example 5 in a 3.5% NaCl solution is 18 μA / cm. 2 It can be seen that the numerical value is larger than that of the first embodiment.
[0019] Example 2 The components of the highly enriched rare earth permanent magnet were measured in atomic percentage, and the atomic percentage was [(Pr 0.2 Nd 0.8 ) 0.55 (La 0.15 Ce 0.85 ) 0.45 ] 15Fe 77.8 (Ga 0.6 Cu 0.2 Al 0.25 Nb 0.32 )1B 5.83 During the high-temperature oxidation reaction in the heat treatment furnace, the temperature is set to 850°C, the reaction time is set to 5h, and the oxygen partial pressure is set to 0.5Pa. The thickness of the thin film of rare earth oxide formed on the original position of the magnet surface is ~3μm. According to the measurement results of the AMT-4 permanent magnet characteristic measurement device, it can be seen that the remanence of the magnet subjected to the surface oxidation treatment is 12.4kG, and the coercive force is 7.2kOe. According to the measurement results of the AMETEK electrochemical workstation, the corrosion current of the magnet subjected to the surface oxidation treatment in 3.5% NaCl solution is 12μA / cm 2 It can be seen that.
[0020] Comparison 6 The difference between Comparative Example 6 and Example 2 is that the highly enriched rare earth permanent magnet of Comparative Example 6 was not subjected to high temperature oxidation. Measurement results using an AMT-4 permanent magnet characteristic measuring device showed that the magnet of Comparative Example 6 had a residual magnetism of 12.4 kG and a coercive force of 5.6 kOe, both of which were lower than those of Example 2. Measurement results using an AMETEK electrochemical workstation showed that the corrosion current of the magnet of Comparative Example 6 in a 3.5% NaCl solution was 135 μA / cm. 2 It can be seen that the value is ten times higher than that of Example 2.
[0021] Example 3 The components of highly enriched rare earth permanent magnets are measured in atomic percentage, and the atomic percentage is [Nd 0.75 (Y 0.1 Ce 0.9 ) 0.25 ] 15.5 (Fe 0.92 Co 0.08 ) 76.9 (Cu 0.2 Ga 0.1 Al 0.35 S 0.2 Nb 0.15 ) 1.5 B6.1 During the high-temperature oxidation reaction in the heat treatment furnace, the temperature is set to 700°C, the reaction time is set to 5h, and the oxygen partial pressure is set to 0.5Pa. The thickness of the thin film of rare earth oxide formed on the original position of the magnet surface is ~800nm. According to the measurement results of the AMT-4 permanent magnet characteristic measurement device, it can be seen that the remanence of the magnet subjected to the surface oxidation treatment is 12.6kG, and the coercive force is 12.2kOe. According to the measurement results of the AMETEK electrochemical workstation, the corrosion current of the magnet subjected to the surface oxidation treatment in 3.5% NaCl solution is 20μA / cm 2 It can be seen that.
[0022] Comparison 7 The difference between Comparative Example 7 and Example 3 is that the highly enriched rare earth permanent magnet of Comparative Example 7 was not subjected to high temperature oxidation. Measurement results using an AMT-4 permanent magnet characteristic measuring device showed that the magnet of Comparative Example 7 had a residual magnetism of 12.3 kG and a coercive force of 10.1 kOe, both of which were lower than those of Example 3. Measurement results using an AMETEK electrochemical workstation showed that the corrosion current of the magnet of Comparative Example 7 in a 3.5% NaCl solution was 250 μA / cm. 2 It can be seen that the value is increased by more than ten times compared to the value in Example 3.
[0023] Example 4 The components of highly enriched rare earth permanent magnets are measured in atomic percentage, and the atomic percentage is [Nd 0.35 (Y 0.3 Ce 0.7 ) 0.65 ] 16.0 (Fe 0.87 Co 0.13 ) 75.9 (Cu 0.3 Ga 0.1 Al 0.35 S 0.35 Zr 0.05 Nb 0.15 ) 1.5 B 6.15During the high-temperature oxidation reaction in the heat treatment furnace, the temperature is set to 900°C, the reaction time is set to 3h, and the oxygen partial pressure is set to 0.01Pa. The thickness of the thin film of rare earth oxide formed on the original position of the magnet surface is ~1μm. According to the measurement results of the AMT-4 permanent magnet characteristic measurement device, it can be seen that the remanence of the magnet subjected to the surface oxidation treatment is 11.5kG, and the coercive force is 7.1kOe. According to the measurement results of the AMETEK electrochemical workstation, the corrosion current of the magnet subjected to the surface oxidation treatment in 3.5% NaCl solution is 35μA / cm 2 It can be seen that.
[0024] Comparison 8 The difference between Comparative Example 8 and Example 4 is that the highly enriched rare earth permanent magnet of Comparative Example 8 was not subjected to high temperature oxidation. According to the measurement results using an AMT-4 permanent magnet characteristic measuring device, the magnet of Comparative Example 8 had a remanence of 11.2 kG and a coercive force of 6.1 kOe, which are lower than those of Example 4. According to the measurement results using an AMETEK electrochemical workstation, the corrosion current of the magnet of Comparative Example 8 in a 3.5% NaCl solution was 580 μA / cm 2 It can be seen that the value is ten times higher than that in Example 4.
Claims
1. By oxidation treatment at a temperature of 700 to 1000°C, the oxygen partial pressure during oxidation is reduced to 10 -2 A method for increasing the corrosion resistance of a rare earth permanent magnet by oxidation treatment, comprising the steps of: setting a pressure of 10 Pa to 10 Pa; forming a thin film of rare earth oxide at the original position on the surface of a rare earth permanent magnet containing one or more of La, Ce, and Y elements; and setting the reaction time for an oxidation reaction in a heat treatment furnace to 0.2 to 5 h.
2. 2. The method for increasing the corrosion resistance of rare earth permanent magnets by oxidation treatment according to claim 1, characterized in that the thickness of the rare earth oxide thin film is freely changed within the range of 10 nm to 100 μm.
3. The components of the rare earth permanent magnet are measured in atomic percentage, and the atomic percentage is (REaRE'1-a)x(FebM1-b)100-x-y-zM'yBz, in which RE is any one or more of La, Ce, and Y elements, RE' is any one or more of lanthanides other than La, Ce, and Y, Fe is iron element, and M is any one or two of Co and Ni.
2. The method for increasing corrosion resistance of rare earth permanent magnets by oxidation treatment according to claim 1, wherein M' is one or more of Nb, Zr, Ta, V, Al, Cu, Ga, Ti, Cr, Mo, Mn, Ag, Au, Pb, and Si elements, B is boron element, and a, b, x, y, and z satisfy the following formulas: 0.25≦a≦1, 0.8≦b≦1, 12≦x≦18, 0≦y≦2, 5.5≦z≦6.5.
Citation Information
Patent Citations
Permanent magnet
JP1986159708A
Permanent magnet having improved corrosion resistance and its manufacture
JP1988062204A
Surface treatment of permanent magnet
JP1989318209A
High temperature passivation of rare earth magnets
WO1999002337A1